COVID-19 Vaccines, Healthcare Policies and Stock Markets: Are There Winners and Losers? - Diaz RF; Herrador-Alcaide TC; Sanchez-Robles B (Dove Medical Press, 2023)
Ricardo F Diaz,1 Teresa C Herrador-Alcaide,2 Blanca Sanchez-Robles1 1Department of Economic Analysis, Universidad Nacional de Educación a Distancia, Madrid, Spain; 2Department of Financial Economics and Accountancy, Universidad Nacional de Educación a Distancia, Madrid, SpainCorrespondence: Blanca Sanchez-Robles, Department of Economic Analysis, UNED, P. Senda del Rey, 11, Madrid, 28040, Spain, Email bsanchez-robles@cee.uned.esPurpose: This paper focuses on the stock market performance of a set of biopharmaceutical companies listed in the US stock exchange in response to news about the unfolding of the COVID pandemic and the development of COVID-19 vaccines.Methods: We analyze the short-term impact of some episodes by means of event analysis. We consider two categories of events: news related to the expansion of the pandemic and information about the development of COVID-19 vaccines.Results: We find that the impact during the first months of the pandemic news impacted the returns of the pharmaceutical firms, but the effect was not large, in general. The only exceptions are two small biotechnological firms, Moderna and Novavax, are exceptions since they registered large positive abnormal returns, which vanished over time. Encouraging announcements about the success of Phase III results had a positive impact the share prices of Pfizer, Moderna and Novavax. Our results also suggest that the emergency authorization provided by the US regulatory agency to the Pfizer vaccine was anticipated several days in advance and welcomed by the market. The announcement of a deal to supply vaccines between Moderna and the European Commission have generated large positive returns for this company.Conclusion: Our findings have policy implications. First, financial markets have supported and reinforced government strategies to fight the pandemic, characterized by funding of promising projects, building diversified vaccine portfolios and expediting approvals by regulatory agencies. Second, our findings suggest that not all drug developers have automatically obtained large profits from the design and manufacturing of COVID-19 vaccines, according to the behaviour of stock prices. These results cast doubts over attempts to discredit the efficacy of COVID-19 vaccines with the argument that they are primarily a means to obtain large and quick profits by pharmaceuticals, or than vaccination campaigns are driven by economic goals rather than by public health considerations.Keywords: event analysis, COVID-19 vaccines, phase III, clinical trials, pharmaceutical industry, stock markets